Strategi Branding Online melalui Konten Kreatif untuk Meningkatkan Daya Saing Produk Rawon Kluwek Surabaya - Ihsan Fauzi; Ni Made Ida Pratiwi (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to develop an online branding strategy for Rawon Kluwek Surabaya through the creation of creative content to enhance the product's competitiveness in the culinary market. Through this community service activity, business owners were trained in techniques for creating engaging visual content, managing social media, and implementing storytelling to strengthen brand image. The results of this activity show that business owners experienced an improvement in their skills in producing more professional product photos and videos, as well as in managing their social media accounts more effectively. Increased interaction and engagement from consumers on social media demonstrate that creative content successfully attracted a wider audience, which in turn contributed to improving the product's competitiveness. Based on the evaluation conducted, this activity has had a positive impact on strengthening Rawon Kluwek Surabaya’s position in an increasingly competitive market. However, there are still challenges in maintaining consistent content production, which requires further attention to ensure the sustainability of this branding strategy.